The Effectiveness of Nonprescription Drug Labels in the United States: Insights from Recent Research and Opportunities for the Future - Jesse R. Catlin; Eric P. Brass (MDPI AG, 2018)
Despite providing a consistent and comprehensible format for over-the-counter (OTC) drug communication, research suggests important limitations in the communication effectiveness of the Drug Facts Label required on OTC drugs in the United States. This literature is reviewed and some of these critical limitations of the Drug Facts Label (DFL) highlighted. These include difficulty communicating complex information that requires integration of multiple pieces of label information and limited adaptability to serve the unique needs of individual populations (e.g., low literacy or older consumers). Potential ways to improve the DFL’s communication effectiveness are identified along with complementary opportunities to improve OTC drug communication by leveraging the role of pharmacists and use of adjunctive technologies.